O.9.2Oncology nurses' perceptions of advance directives for patients with cancer: Presenter(s): Breanne Hobden, University of Newcastle, Australia. (April 2023) - Bryant, Jamie; Waller, Amy; Shepherd, Jan; Sanson-Fisher, Rob
Abstract : Background: Advanced care planning (ACP) is important for all adults but particularly for individuals diagnosed with a potentially life-limiting illness, such as cancer. As nurses often form the bridge between patient and doctor, they have both clinical and patient-level expertise which places them in a unique position to assist with the ACP process. Understanding nurses' attitudes and beliefs surrounding ACP may highlight key barriers or enablers to their uptake. This study examined oncology nurses' perceptions of the impact of advance directives (i.e., formalised document of ACP wishes) on oncology patients' end-of-life care. Methods: Nurses (n = 104), who were members of an oncology nursing society or worked in a large metropolitan cancer center, completed a cross-sectional survey assessing perceptions of advance directives. Findings: There was high agreement that advance directives (i) make decisions easier for family (87%) and providers (82%); (ii) are doctors' responsibility to implement (80%); (iii) reduce unwanted aggressive treatment in the last weeks of life (80%); (iv) protect patient autonomy (77%); and (v) increase the likelihood of dying in a preferred location (76%). There was moderate or low agreement that advance directives (i) are accessible when needed (60%); (ii) are oncology nurses' responsibility to implement (46%); (iii) are always followed (41%); (iv) reduce the likelihood of pain in the last weeks of life (31%); (v) contain difficult to follow statements (30%); and (vi) have no impact on comfort in the last weeks of life (15%). Discussion: This research indicates that nurses perceive ADs to have several positive impacts for health professionals, patients, and their families. Nevertheless, there remains uncertainty around accessibility and implementation. Guidelines and education about advance directive processes in oncology could improve person-centered end-of-life care.